ANALISIS DEL NUEVO ENFOQUE DE EVALUACIÓN DEL SISTEMA DE CONTROL INTERNO EN EL ILUSTRE MUNICIPIO DEL CANTÓN OÑA - PROVINCIA DEL AZUAY PROPUESTA - Masache narváez, Dra. María Dolores (2012)
The thesis work that is presented is related with the ANALYSIS OF THE NEW FOCUS OF EVALUATION OF THE SYSTEM OF INTERNAL CONTROL IN THE ILLUSTRIOUS MUNICIPALITY OF THE CANTON OÑA - COUNTY OF THE PROPOSED AZUAY, the objectives were guided to propose a basic methodology for the identification of the fundamental tools as they are the key controls that are the base of the Evaluation of the System of Internal Control by means of the report I SEW, it allows to establish techniques to evaluate the execution and to validate the proposal in the Illustrious Municipality of the Canton Oña of the County of the Azuay, the analysis allowed to carry out a study of the elements of the New Focus of Evaluation of the System of internal Control with the purpose of proposing a correct application in the development of an audit. The results allow to evidence that in the Illustrious Municipality of the Canton Oña of the County of the Azuay, they have not been carried out studies on the Internal Control, to such a point that the main elements of the Internal Control are ignored by the responsible ones of to implement it and to execute it inside the entity, the fixed assets especially have a faulty control, what causes wastes and wrong use of the same ones, the unit of internal audit has not carried out consistent evaluations on the institutional administration, since newly it was created in the entity, in spite of being a municipality with many years of creation, the lack ofmanuals of procedures have determined that the servants don't complete with the functions and responsibilities to them commended, with clear violation to the effective legal dispositions in this entity, therefore and I eat definitive conclusion one can affirm that the System of Internal Control implanted in the institution with the purpose of safeguarding the material and financial human resources, presents series and that the faulty control also redounds in the non dependability of the presented information and he/she doesn't allow to make decisions guessed right on the part of those who direct the Municipality of the Canton at the moment Oña. The methodology of the analysis of the Internal Control by means of the System SEWS that he/she thinks about as proposal alternative, it is based on the correct identification of controls keys that you/they allow to carry out a technical and reliable evaluation of the control procedures in all the levels of the diverse administrative and operative areas of the municipality with the purpose of to be competitive and to respond to the new institutional demands, he/she is born this way a new application method and execution of internal control where you offers a common structure which is documented with the presentation of the proposal. The conclusions that were obtained to the I finish of the work it determines that the implementation of the internal control implies that each one of its components is applied to each administrative area of the municipality in a permanent integrative and dynamic process, like previous step will settle down the objectives, politicians and related strategies to each other with the purpose of guaranteeing the organizational development and the execution of the institutional goals.